Analisis Pengaruh Kualitas Pelayanan Kesehatan terhadap Kepuasan dan Loyalitas Pasien RSUD Tgk. Chik Ditiro Sigli Kab. Pidie Provinsi Aceh - Jam’an .; A. Rahim Matondang; Nazaruddin Matondang (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2017)
This study was conducted to find out : (1) Influence of service quality of RSUD Tgk. Chik Ditiro Sigli on patient satisfaction of RSUD Tgk. Chik Ditiro Sigli. (2) Influence of service quality of RSUD Tgk. Chik Ditiro Sigli on patient loyalty RSUD Tgk. Chik Ditiro Sigli. (3) The influence of patient satisfaction on patient loyalty RSUD Tgk. Chik Ditiro Sigli. Used method study Explanatory research with Structural Equation Mode continue made interpretation, conclusions and suggestions. treatment on 210 Patients by giving observation sheet which consist of 65 Questions which is distributed on 14 manifest variable in 3 latent variable. found : (1) The quality of service is measured by tangible, reliability, responseiveness, assurance, convenience (empathy) give a contribution to the satisfaction of patients RSUD Tgk. Chik Ditiro Sigli of 0.173. (2) Service quality is measured by tangible, reliability, responsiveness, assurance and empathy giving positive influence to patient loyalty of RSUD Tgk. Chik Ditiro Sigli 0.219. The patient satisfaction was measured by idiosyncrasy, conformity, consistent and aesthetics giving positive influence on Patient Loyalty of RSUD Tgk. Chik Ditiro Sigli. It showed that the average value of observation sheet is 0.270.